Developing the charging infrastructure for electric cars. Northwestern Italy facing European targets - Staricco, Luca; Sammartino, Angelo (TeMA - Journal of Land Use, Mobility and Environment, 2025)
<span class="NormalTextRun SCXW146566213 BCX0" data-ccp-parastyle="Abstract" data-ccp-parastyle-defn="{"ObjectId":"fe0017e7-5150-5d7c-ac64-5f509ec11579|1","ClassId":1073872969,"Properties":[201342446,"1",201342447,"5",201342448,"1",201342449,"1",469777841,"Tahoma",469777842,"Tahoma",469777843,"Calibri",469777844,"Tahoma",201341986,"1",469769226,"Tahoma",268442635,"18",469775450,"Abstract",201340122,"2",134234082,"true",134233614,"true",469778129,"Abstract",335572020,"1",335551547,"1033",335559740,"276",201341983,"0",335559739,"0",335551550,"6",335551620,"6",469778324,"Normal"]}">This paper analyzes the development of charging infrastructure for electric light-duty vehicles in northwestern Italy in relation to the targets set by EU Regulation 2023/1804. This regulation introduces two types of requirements for Member States: fleet-based targets, related to the number of registered electric and hybrid vehicles, and distance-based targets, which require adequate coverage along the TEN-T road network. Using data from national and European platforms, the study assesses the degree of alignment with these targets at the provincial levels. The results reveal a strong regional variation in infrastructure adequacy: while some provinces exceed the required power output, others - – particularly in rural or mountainous areas -– remain underpowered. Regarding the distance-based dimension, 71% of the TEN-T core network and 54% of the comprehensive network already meet the 2027 EU targets. The paper applies a Greedy optimization algorithm to propose cost-effective upgrade strategies for existing charging pools, showing that full compliance is achievable with limited interventions. The discussion highlights the critical role of policy incentives and governance, emphasizing the need to empower regional authorities and rebalance funding between vehicle acquisition and infrastructure development. The study concludes by offering policy recommendations to foster equitable and sustainable deployment of electric mobility infrastructure.